Experimental and numerical study of self-locking adaptable inter connection for modular steel structures - Nadeem, Gohar; Safiee, Nor Azizi; Bakar, Nabilah Abu; Karim, Izian Abd; Mohd Nasir, Noor Azline (Elsevier, 2023)
Compared to conventional steel construction, modular steel construction (MSC) is different. Instead of having a high degree of connectivity, the modules are connected at their corners only by inter-modular connections (IMC), which are the most vulnerable points of failure and require extra operation spaces. An adaptable connection was proposed in this study, and the working mechanism of the proposed connection was presented. Three full-scale connections consisting of square hollow section (SHS) members were tested under monotonic and cyclic loads to determine the seismic performance. The results showed that reinforced joints sustained 80% of the limit of the rigid joint at an inter-story drift ratio of 0.04 radian and satisfied the condition for strong column weak beam joint mechanism. Non-linear Finite Element Analysis (FEA) was conducted on this adaptable connection with a parametric study to study more influences of other related parameters. The findings indicated that the gap produced between connection and column under higher displacement was sensitive to the outer bolt and spring pin. This gap could be further reduced by increasing the number of outer bolts and by reducing tolerance between adapter and column walls.